How social advertising affects the buying behaviour of malaysian consumers? Testing the moderating effects of gender and education - Fazal Ur Rehman; Viktor Prokop; Bestoon Othman; Farwida Javed; Sadia Ijaz (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
This study examines the influence of social advertising on the buying behaviour of Malaysian consumers along with the moderating role of gender and education. We use our own Primary data that were collected through questionnaire-based survey from the shoppers at various shopping malls of fashion clothing brands at Kuala Lumpur and State Johor in Malaysia. The collected data were analyzed by using step wise regression and correlation statistics to find results. The findings revealed that social advertising, informativeness, entertainment, credibility, ease of use, contents, and gender have positive effects on the buying behaviour of Malaysian consumers toward the fashion clothing brands. By contrast, we find negative effects of privacy and education. Next, we show that gender has moderating effects in the defined context. The main contribution of this study is the assessment of the effects of some unique and influential factors of social advertising on the buying behaviour among Malaysian consumers towards the fashion clothing brands. In addition, this study has also assessed the moderating effects of gender and education to extend the body of knowledge in that area. Finally, we present practical implications for managers.
Keywords: M15; P46; 330; Social Advertising; Consumer Behavior; Gender; Education; Fashion Brands